Clinical Outcomes in Chronic Conditions: Findings from a Homeopathy Teaching Clinic using the MYCaW Instrument - Gray, Alastair C.; Luketic, Christine D.; Pracjek, Parker; Straiges, Denise (Homeopathy, 2024)
Background The Academy of Homeopathy Education is a US-based accredited teaching institution offering homeopathy education services to professional and medically licensed homeopathy students. This study reports on clinical outcomes from the teaching clinic from 2020 to 2021.Methods Data collected using the patient-generated outcome measure, the Measure Yourself Concerns and Wellbeing (MYCaW), were anonymized. Mean MYCaW values for initial and subsequent consultations were analyzed for the degree of change across the intervention period in 38 clients. Each client listed up to two complaints. MYCaW scores between initial and subsequent consultations were analyzed for the degree of change (delta) across the intervention period.Results A total of 95 body system-related symptoms were analyzed for change in intensity following the homeopathic intervention. Statistically significant improvements in the intensity of main symptoms were observed between initial and subsequent follow-ups. The main symptom scores showed a mean change in intensity (delta MYCaW) of −0.79 points (95% confidence interval (CI), −1.29 to −0.29; p = 0.003) at first follow-up, a mean change of −1.67 points (95% CI, −2.34 to −0.99; p = 0.001) at second follow-up compared with the initial visit, and a mean change of −1.93 points (95% CI, −3.0 to −0.86; p = 0.008) at third follow-up compared with the initial visit. For clients with four or more follow-ups, the mean delta MYCaW was −1.57 points (95% CI, −2.86 to −0.28; p = 0.039).Conclusion Statistically significant improvements as well as some clinically meaningful changes in symptom intensity were found across a diverse group of individuals with a variety of long-term chronic conditions. The improvement was evident across different body systems and different levels of chronicity. There are limitations to the generalizability of the study due to the research design. Further research and investigation are warranted given the promising results of this work.
Keywords: homeopathy; MYCaW; clinical outcomes; clinical settings; Academy of Homeopathy Education